PENGARUH BRAND IMAGE, ELECTRONIC WORD OF MOUTH (E-WOM) DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN TIKET KONSER WORLD TOUR REVERIE IN JAKARTA (STUDI KASUS PENGGEMAR IDOL K-POP BAEKHYUN EXO) - Maria Chalista; Muhammad Robi Nurwahyudi (MANAJEMEN DEWANTARA, 2026)
This research aims to analyze the influence of brand image, electronic word of mouth (e-WOM), and price on the decision to purchase World Tour reverie in jakrta concert tickets on EXO’s Baekhyun fans. The study used a quantitative approach with purposive sampling technique for 50 respondents who had purchased concert tickets. Data were collected through questionnaires and analyzed using SPSS 27 with multiple linear regression analyses. Research results show that partial brand images have a significant effect on purchasing decisions, while e-WOM and pricing have no significant effect. However, simultaneous brand iamge, e-WOMs, and prices have a significant effect on the decision to purchase concert tickects.